Comparison of Cognitive Function in Children with Stunting and Children with Undernutrition with Normal Stature - Setyo Handryastuti; Hardiono D. Pusponegoro; Surastuti Nurdadi; Anita Chandra; Feka A. Pramita; Amanda Soebadi; Ivan R. Widjaja; Achmad Rafli (Journal of Nutrition and Metabolism)
Background. Stunting is the impaired growth and development that children experience from poor nutrition, repeated infection, and inadequate psychosocial stimulation. Children are defined as stunted if their height-for-age is more than two standard deviations below the WHO Child Growth Standards median. According to the Indonesia Basic National Health Survey 2013, Indonesia’s stunting prevalence reached 37.2%. Various studies have shown that impaired cognitive development is found in children with stunting and undernutrition. This study aims to determine cognitive development in stunted and undernutrition with normal stature children using the Bayley Scale of Infant Development III (Bayley-III). Methods. A cross-sectional study on 51 children aged one month to 3 years who fulfilled the inclusion criteria and who visited the outpatient clinic of Dr. Cipto Mangunkusumo National General Hospital from June 2017 to January 2018 was performed. Cognitive development was assessed using the Bayley Scale of Infant Development, Third Edition (Bayley-III). Results. 26 children with stunting and 25 children with undernutrition with normal stature participated in this study. There was a statistically nonsignificant trend toward lower median score percentiles in the stunted group compared to that in the undernourished with normal stature group in the motor (median (range) 1 (0.1–75) vs. 4 (0–79); p=0.183), cognitive (12.5 (0.1–75) vs. 16 (0.1–99.9); p=0.550), and adaptive behavior (7 (0.1–75) vs. 12 (0.1–58); p=0.657) domains. Conclusions. There is a trend toward lower cognitive, motor, and adaptive behavior abilities in stunted children compared to undernourished children with normal stature which needs further study. In addition, children with undernutrition have below-average abilities across all domains even before stunting has occurred.